2018
DOI: 10.3389/fendo.2018.00196
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Chaperones in the Brain: Safeguarding Brain Health and Metabolism?

Abstract: The brain orchestrates organ function and regulates whole body metabolism by the concerted action of neurons and glia cells in the central nervous system. To do so, the brain has tremendously high energy consumption and relies mainly on glucose utilization and mitochondrial function in order to exert its function. As a consequence of high rate metabolism, mitochondria in the brain accumulate errors over time, such as mitochondrial DNA (mtDNA) mutations, reactive oxygen species, and misfolded and aggregated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 178 publications
0
42
0
Order By: Relevance
“…Synthesized ATP by brain cell mitochondria fuels energy-dependent intracellular reactions (such as ion transport, vesicle release, and neurotransmitter biosynthesis and uptake), contributing to intracellular signaling, synaptic process, and brain function. Most defects of mitochondria are linked to neurodegenerative and metabolic diseases 123 . Previous findings from animal studies suggest that mitochondria appear to be a major target of ethanol toxicity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesized ATP by brain cell mitochondria fuels energy-dependent intracellular reactions (such as ion transport, vesicle release, and neurotransmitter biosynthesis and uptake), contributing to intracellular signaling, synaptic process, and brain function. Most defects of mitochondria are linked to neurodegenerative and metabolic diseases 123 . Previous findings from animal studies suggest that mitochondria appear to be a major target of ethanol toxicity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, brain tissue needs mitochondria to maintain its normal function and energy consumption. Mitochondrial dysfunction in the brain is associated with neurodegenerative diseases [15,33,34]. In addition, energy consumption in the heart is similar to that of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Many compounds have caused mitochondrial toxicity and these organelles has become one of the research targets [13,14]. Brain and heart tissues depend on mitochondria for their high energy consumption and maintenance of their normal function [15,16]. Research has shown that mitochondria are one of the targets of PPARγ agonists [3,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Proteostasis is the maintenance of the proteome ensuring that all proteins are correctly folded, localized, and concentrated for their function. Mitostasis refers specifically to mitochondrial proteostasis [ 77 ]. Mitochondria possess both circular DNA and a transcription–translation machinery [ 78 ].…”
Section: Oxidative and Nitrosative Modifications Of Mitochondrial mentioning
confidence: 99%